The Crucial Role of Computed Tomography (CT) in Early and Analytical Diagnosis of Lung Cancer: An Analytical Study (Comprehensive Journal of Science, 2025)
This study aims to explore and evaluate the pivotal role of Low-Dose Computed Tomography (LDCT) as a crucial and effective screening and early diagnostic tool for lung cancer, correlating its findings with histological confirmation (biopsy). The study adopted a descriptive, analytical, and clinical methodology, initially involving 310 cases subjected to screening, among which 194 cases were confirmed to have lung cancer and were classified demographically. Demographic results showed that males and the 60-69 age group were most susceptible. Clinically, reliable international evidence, applied to the study population, confirms that early detection via CT significantly increases the rate of diagnosis in early stages (I and II), dramatically enhancing cure rates. The study highlights the critical importance of CT as a diagnostic tool and recommends implementing periodic screening programs for high-risk groups.